2017
DOI: 10.1002/2211-5463.12263
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophagoides pteronyssinus lytFM encoding an NlpC/P60 endopeptidase is also present in mite‐associated bacteria that express LytFM variants

Abstract: The bodies and faecal pellets of the house dust mite ( HDM ), Dermatophagoides pteronyssinus , are the source of many allergenic and nonallergenic proteins. One of these, the 14‐ kD a bacteriolytic enzyme Lyt FM , originally isolated from the spent HDM growth medium, may contribute to bacteriolytic activity previously detected by zymography at 14 kD a in the culture supernat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In family G2, the bacterial homologues are mostly from Firmicutes, and in families S73 and S74, from Proteobacteria. Families C40, M23, M60 and N10 also have eukaryote and/ or archaean homologues, presumably the result of horizontal gene transfers, but only the C40 peptidase LytFM from the house dust mite (Dermatophagoides pteronyssinus) has been characterized [32]. The only peptidase family that contain homologues from dsDNA virus and eukaryotes (in addition to those listed above for mimiviruses) is C19.…”
Section: Peptidase Families With An Origin In Virusesmentioning
confidence: 99%
“…In family G2, the bacterial homologues are mostly from Firmicutes, and in families S73 and S74, from Proteobacteria. Families C40, M23, M60 and N10 also have eukaryote and/ or archaean homologues, presumably the result of horizontal gene transfers, but only the C40 peptidase LytFM from the house dust mite (Dermatophagoides pteronyssinus) has been characterized [32]. The only peptidase family that contain homologues from dsDNA virus and eukaryotes (in addition to those listed above for mimiviruses) is C19.…”
Section: Peptidase Families With An Origin In Virusesmentioning
confidence: 99%
“…Consistent with relatively ancient LGT event(s) into the Trichomonas lineage, analyses of GC% profile variation of the nine scaffolds encoding the nine TvNlpC/P60 genes, we observed that seven genes were located in segments with average GC% composition characteristic of the T. vaginalis genome (~31-32 GC%) and were not located close to segmentation points (S1 Table and S6 Fig). This is in contrast to the relatively recent candidate LGT likely derived from a bacterial donor from the urogenital tract identified on a ~53 kbp T. vaginalis genome sequence scaffold [35]. A segment of ~34 kbp encodes 27 proteins highly similar (range: 79–98% identity) and with long stretches of gene synteny with the bacteria Peptoniphilus harei .…”
Section: Discussionmentioning
confidence: 73%
“…One gene derived from a ground water metagenome [33], member of the major bacterial TM6 lineage (accession KKP35888.1), was included as it clustered within a well-supported clan that included the sequence from the free-living protist Acantamoeba castellanii , a published candidate LGT for this species [34] (Fig 1). Additional published NlpC/P60 candidate LGTs in eukaryotes were also considered including genes from Fungi and mites [35], providing a far more appropriate phylogenetic framework to investigate the tempo and mode of LGT for all nine TvNlpC/P60 sequences compared to published analyses, which only considered one TvNlpC/P60 sequence and bacterial sequences [14,18].…”
Section: Resultsmentioning
confidence: 99%
“…The unexpected discovery of an endo-β-1,3 glucanase in the Antarctic springtail, Cryptopygus antarcticus was explained by horizontal gene transfer (HGT) (Song et al, 2010). Thus, the presence of β-1,3 glucanases in the genome of D. pteronyssinus may also point to acquisition by HGT, as HGT has been seen previously in this species (Tang et al, 2017).…”
Section: Introductionmentioning
confidence: 77%